From budget design to budget execution in fragile states: Inverted fiscal discipline and Institutional prioritisation - Fakaba Sissoko, Étienne; Bayo, Pierre; Dembélé, Khalid (Revue Internationale des Sciences de Gestion, 2026)
In fragile states, formal fiscal discipline does not necessarily translate into the effective protection of social functions. This article examines this dissociation through an institutional analytical approach based on the case of Mali over the period 2019–2024. Drawing on national administrative budget data, it links ex ante budgetary design and ex post budgetary execution through descriptive indicators of execution ratios, execution gaps, and priority drift. The results show that budgetary priorities are already embedded at the design stage and are generally reinforced during execution under liquidity constraints: vital social functions such as health, education, and social protection tend to absorb adjustment pressures, whereas sovereignty-related and administrative expenditures are comparatively protected. The article conceptualises this recurring pattern as inverted fiscal discipline, that is, a configuration in which aggregate fiscal compliance coexists with persistent social fragility. Based on single-country evidence, the findings should be read as identifying an institutional pattern rather than a fully identified causal mechanism. Methodologically, the article contributes a reproducible ex ante/ex post framework for analysing effective budgetary prioritisation in fragile contexts.